Vasculogenic mimicry in non-small cell lung cancer: a systematic review - Shapkina, Valeriia; Shindyapin, Vadim; Burlov, Nikita; Prosekina, Elizaveta; Artemyeva, Anna (Frontiers in Oncology, 2025)
Vasculogenic mimicry (VM), a non-endothelial tumor blood supply mechanism linked to poor prognosis in various cancers, requires consolidated prognostic evaluation in non-small cell lung cancer (NSCLC). This systematic review synthesized evidence on VM’s association with survival outcomes (OS, DFS, PFS) in NSCLC patients. Following PRISMA-ScR guidelines, PubMed and Google Scholar were searched, identifying 19 eligible studies (all in Chinese populations) using immunohistochemistry (CD31/CD34-PAS) for VM detection. Eighteen studies found VM presence (prevalence 13.6%–45.2%) significantly associated with worse survival. Multivariate analyses identified VM as an independent negative prognostic factor, increasing mortality risk (HR 1.542–2.542) and progression risk (HR 2.1–2.4). However, critical limitations included exclusive focus on Asian cohorts, universal retrospective design, inconsistencies and potential artifacts in VM detection, and statistical issues (misreported risk measures, discordant data). While VM correlates with reduced survival in NSCLC, suggesting potential prognostic utility, these limitations - particularly ethnic homogeneity, retrospective bias, methodological heterogeneity, and statistical errors - preclude definitive conclusions. Future prospective studies with standardized VM assessment and diverse populations are essential for validation.